The Effect of Pangasius hypopthalmus Oil on the Memory of Mice (Mus musculus) - Robiatun, Robiatun; Oktiansyah, Rian; Iktibar, Izon (Universitas Islam Jember, 2025)
Fish oil is an essential nutrient that is vital for the human body due to its content of saturated and unsaturated fatty acids, particularly omega-3. The Pangasius fish (Pangasius hypopthalmus) is known to have a relatively high content of omega-3 compared to other freshwater fish. Omega-3 fatty acids are crucial for neuronal growth, thereby influencing memory function. This study aimed to investigate the effect of Pangasius fish oil on the memory of mice (Mus musculus). The experimental design was a completely randomized design involving 24 mice, divided into six treatment groups (P0: Control, P1: 0.0016 ml/g weight/day, P2: 0.0033 ml/g weight/day, P3: 0.005 ml/g weight/day, P4: 0.0066 ml/g weight/day, P5: 0.0083 ml/g weight/day), with four repetitions for each treatment administered over seven days. The parameter observed was the number of mice that correctly explored all arms of the Y-maze. The observations indicated that fish oil has a tendency to influence the memory of mice.